Oxidative Stress and Antioxidant Therapy in Pulmonary Hypertension - Paula Poyatos; Miquel Gratacós; Kay Samuel; Ramon Orriols; Olga Tura-Ceide (MDPI AG, 2023)
Pulmonary hypertension (PH) is a progressive disease characterized by elevated artery pressures and pulmonary vascular resistance. Underlying mechanisms comprise endothelial dysfunction, pulmonary artery remodeling and vasoconstriction. Several studies have shown evidence of the critical role of oxidative stress in PH pathophysiology. Alteration of redox homeostasis produces excessive generation of reactive oxygen species, inducing oxidative stress and the subsequent alteration of biological molecules. Exacerbations in oxidative stress production can lead to alterations in nitric oxide signaling pathways, contributing to the proliferation of pulmonary arterial endothelial cells and smooth muscle cells, inducing PH development. Recently, antioxidant therapy has been suggested as a novel therapeutic strategy for PH pathology. However, the favorable outcomes observed in preclinical studies have not been consistently reproduced in clinical practice. Therefore, targeting oxidative stress as a therapeutic intervention for PH is an area that is still being explored. This review summarizes the contribution of oxidative stress to the pathogenesis of the different types of PH and suggests antioxidant therapy as a promising strategy for PH treatment.